Health shocks and health behavior: a long-term perspective - Christian Bünnings; Irina Simankova; Harald Tauchmann (The European Journal of Health Economics, 2025)
Several empirical papers suggest that individuals improve health-related behaviors in response to adverse shocks to physical health. However, little evidence exists regarding the questions of (i) how long-lasting these behavioral responses are and (ii) whether individuals respond similarly to mental health shocks. Using individual-level survey data from Germany and combining regression augmented inverse-probability weighting with machine learning prediction algorithms, we compare individuals hit by such shocks to undisturbed individuals up to fifteen years after that shock. The analysis confirms earlier findings that individuals experiencing a sharp deterioration of physical health immediately improve their health-related behaviors in terms of eating more healthily and being less likely to smoke. Contrarily, doing sports is negatively affected. We further find that the immediate response to shocks on mental health is weaker, with the exception of smoking. Tobacco consumption on average becomes more likely after a shock to mental health. We further find that the immediate response to shocks on mental health is weaker, with the exception of smoking behavior, which on average worsens after such kind of a shock. Yet the analysis does not reveal long lasting persistent effects. Significant differences in health behaviors are rarely found more than two years after the shock.
Keywords: I12; D12; 610; Health behavior; Health shock; MCS; PCS; Long-term; Double/debiased machine learning